(untitled) (Annual of the Faculty of Philosophy in Skopje, 2016)
Quality of life (QOL) is associated with human values including happiness, satisfaction, general feelings of well-being and opportunities to achieve personal potential. It is a multidimensional phenomenon composed of core domains and elements that are influenced by personal characteristics and environmental. The aim of this paper is to determine whether there is a difference between the Quality of life ofpeople with and without disability in the Republic of Macedonia. A total of 136 people without disability and 60 people with disability were included in the study. The World Health Organization’s Quality of Life Questionnaire (WHOQoL- RREF) was used to measure the quality of life. The results showed that the persons with disabilities, included in our study, subjectively have had lower quality of life than the persons without disabilities. Namely, people with disability had statistically lower scores in the psychological domain (p=0.0001), social relationship domain (p=0.0 002) and environmental domain (p=0.0002) compared to people without disability.